Careers in psychology opportunities in a changing world - Kuther, Tara L.; Morgan, Robert D. (Wadsworth Cengage Learning, 2013)
Choosing a major and career -- Clinical and counseling psychology -- School psychology -- Legal and forensic psychology -- Health psychology -- Sport psychology -- Biopsychology, cognitive neuropsychology, and clinical neuropsychology -- Interests in industrial, organizational, and human factors psychology -- Experimental, cognitive, and quantitative psychology -- Social and consumer psychology -- Developmental psychology -- Getting a job after graduation -- Graduate-level careets in psychology -- Getting into graduate school in psychology
Includes bibliographical references (p. 180-189) and index
Keywords: Psychology / Vocational guidance / Textbooks; Psychology / United States; Psychologie; Berufsberatung; USA